Perspective Effects on Recall in a Testimony Paradigm. Issue 4 (2nd October 2018) - Ginet, Magali; Dodier, Olivier; Bardin, Brigitte; Désert, Michel; Greffeuille, Catherine; Verkampt, Fanny
Abstract: The two present studies examined the influence of perspective instructions given during encoding and retrieval on the recall of a visual event. Participants viewed slides or a film depicting a day in the life of a man. Before viewing the to-be-remembered event, they were instructed to adopt the perspective of an alcoholic vs. an unemployed man vs. no perspective (Experiment 1), or of an unemployed man vs . no perspective (Experiment 2). Participants in the first study were interviewed twice, with the second recall being preceded by either a change perspective instruction or without any specific instruction. In the second study, participants were interviewed using either a cognitive interview (CI) or a CI without the change perspective instruction. Results showed that adopting a perspective during encoding impaired recall performance and failed to demonstrate a significant benefit of the change perspective instruction. The theoretical and practical implications of these results are discussed.